Enhancing Luminous Efficacy of White Led Lamp Using Ca2MgSi2O7:Eu2+ Phosphor - Doan Quoc Anh Nguyen (Journal of Advanced Engineering and Computation, 2018)
Along with the rapid development of science and technology in today's society, lighting technology, especially white light-emitting diodes (WLEDs), has become a critical and essential element in almost every field of our daily life. Therefore, the enhancement of luminous efficiency has become an important objective in the production of white LEDs to serve the needs of customers. This paper presents the influence of Ca2MgSi2O7:Eu2+ green luminescent phosphor on the light quality of WLEDs. In this work, the green-emitting Ca2MgSi2O7:Eu2+ phosphor is added into the in-cup phosphor configuration, which leads to the varying of the scattering property of this compounding. This is proved through the scattering coefficient from Mie-theory. Besides, the color quality scale which is called CQS index of WLEDs is also verified. The achieved results indicate that the luminous efficacy increases significantly if the Ca2MgSi2O7:Eu2+ concentration is varied. The smaller the Ca2MgSi2O7:Eu2+ size is used, the higher the luminous flux is obtained. However, the CQS can decrease if Ca2MgSi2O7:Eu2+ concentration is adjusted in another direction. Therefore, it is vital to select a suitable concentration and size of Ca2MgSi2O7:Eu2+ for enhancing the luminous efficacy of WLEDs, and the benet of this phosphor in creating white WLED packages is a potential solution for developing LED illumination technology.